Analisis Implementasi Manajemen Strategi Dalam Penentuan Harga Tbs Kelapa Sawit Tahun 2022 Pada Dinas Perkebunan Provinsi Sumatera Utara - Sisca Amini Cahya Agitsna Agitsna; Muhammad Ikhsan Harahap (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
Strategic management is one way to determine a decision, not least in determining the price of Palm Oil FFB at the Plantation Office of North Sumatra Province. In the previous year, palm oil prices decreased which caused farmers to feel slightly disadvantaged, while in 2022 for the period from January 5 to March 2, 2022 the price of palm oil bunches increased in price. Of course, this increase depends on how to carry out a pricing strategy. The purpose of this study was to analyze how the role of strategic management in the decision to determine the price of oil palm FFB. The method used in this study is a qualitative method. The results or conclusions of this study are the Plantation Office of North Sumatra Province, especially in the field of processing and marketing which is in charge of determining prices, conducting a meeting system with related employees to determine the price of oil palm FFB, the employees who participate in determining prices are called the